Characterization of the complete chloroplast genome of Platycodon grandifloras (Campanulaceae: Platycodon), the herbal medicine in China. Issue 1 (2nd January 2019) - Lin, Yanping; Jiang, Shangtong; Yang, Xiaodong
Abstract: Platycodon grandiflorus is the single genus plant in family Campanulaceae, which is distributed in areas of China, Japan, Korea, and Russia. In this study, we assembled and annotated the complete chloroplast genome of P. grandiflorus . The chloroplast genome of P. grandiflorus is 171, 624 bp long, containing a shorter small single-copy region (SSC) of 7, 962 bp, a normal large single-copy region (LSC) of 79, 690 bp and a longer pair of inverted repeat regions (IRs) of 41, 986 bp. The whole chloroplast genome of P. grandiflorus has 146 genes, including 102 protein-coding genes (PCGs), 36 transfer RNA genes (tRNAs), and 8 ribosome RNA genes (rRNAs). The overall nucleotide composition is: A of 30.9%, T of 30.9%, C of 19.3%, and G of 18.9%, with a total G + C content of the chloroplast genome 38.2%. The phylogenetic and genetic analysis showed a close relationship between Platycodon grandiflorus and Codonopsis lanceolata .